Economic Survey of Latin America and the Caribbean 2006-2007 - Economic Commission for Latin America; the Caribbean (United Nations, 2007)
The publication surveys the main economic events and developments of 2006 and the first half of 2007 in the light of the region’s recent economic performance. The fifty-ninth edition of the survey is aimed to provide further inputs for the economic debates concerning means of promoting a rapid, sustainable growth process capable of creating conditions conducive to an improvement in the living conditions in the region. It also describes various aspects of the regions economic growth dynamics. The tables provided in the statistical appendix provide ready access to data for recent years and facilitate the creation of spreadsheets. The edition is supplemented by a CD-ROM.